ANKLE BIOMECHANICS AND JUMP PERFORMANCE IN HEALTHY AND CHRONIC ANKLE INSTABILITY INDIVIDUALS DURING LANDING: A TRIPLE BLIND RANDOMIZED CLINICAL TRIAL OF ANKLE TAPING EFFICACY. Issue 4 (1st February 2017) - Jun, Hyung-pil; Chun, Young-min; Kim, Jin-ah; Baker, Russell; Seegmiller, Jeff; Lee, Sae Yong
Abstract : Background: Clinicians regularly utilize ankle taping procedures to prevent ankle sprains during practice/competition. Though many different ankle taping applications are employed, the effect of these on biomechanics and performance is unknown. Objective: To investigate changes in ankle biomechanics during landing and jump performance with ankle taping. Design: Triple-blind randomized. Setting: University laboratory. Participants: Twenty-eight participants (14 healthy, 14 with chronic ankle instability [CAI]). Interventions: Each participant was assigned to a randomized order of three taping applications (1: Traditional Taping [TT], 2: Mulligan Concept Taping [MT], and 3: Kinesiology Taping [KT]) and performed maximum vertical jump and running-stop jump-landings (3 before and 3 after) each ankle taping application. An eight infrared optical cameras system (Vicon Motion Systems Ltd. Oxford, UK) and force plate (AMTI, Watertown, MA) were used to collect all kinematics and kinetics data during running-stop jump-landing. Main Outcome Measurements: Maximum height of vertical jump and excursion of dorsiflexion (DF) and inversion (IV) of the ankle between 100 ms before and after initial contact (IC). Results: A statistically significant difference for the main effects of tape application [ F (2, 26) =0.06, p =0.94, M±SD: 0.82±12.55(TT), 1.29±8.64 (MT), 0.42±10.31 (MT); F (2, 26) =0.58, p =0.46, M±SD: 0.58±1.38(TT), 0.67±0.65(MT), 0.48±0.97(MT)] and interactions [ F (2, 26) =0.89, p =0.51; F (2, 26) =0.46, p =0.41] on changes of DF and IV were not found regardless of tape application. For MVJ, a statistically significant change across tape application was not found [ F (2, 26) =0.65, p =0.49]; however, a statistically significant interaction on MVJ was found in the CAI group with KT application[ F (2, 26) =3.50, p =0.04, M±SD: 0.30±0.69 [Healthy]; −0.36±0.88 [CAI]). Conclusions: The use of tape did not have any significant impact on ankle biomechanics during landing. Using KT produced a significant change in MVJ in participants with CAI, but the improvement is unlikely to be clinically meaningful. The use of these taping methods to improve ankle biomechanics or improve jump performance in healthy athletes, or those with CAI, is questionable.